2021
DOI: 10.3389/fcimb.2021.766427
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Helicobacter pylori Infection and the Risk of Thyroid Nodule Types: A Multicenter Case-Control Studyin China

Abstract: The prevalence of Helicobacter pylori infection is high worldwide, while numerous research has focused on unraveling the relationship between H. pylori infection and extragastric diseases. Although H. pylori infection has been associated with thyroid diseases, including thyroid nodule (TN), the relationship has mainly focused on potential physiological mechanisms and has not been validated by large population epidemiological investigations. Therefore, we thus designed a case-control study comprising participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…And then, the correlation between H.pylori infection and benign or suspicious TN subtypes were further analyzed in the logistic regression analysis adjusted for potential risk factors. Although the proportion of H.pylori positive population in suspicious TN group was statistically lower than that in negative population, H.pylori infection is not an independent risk factors for either benign or suspicious TN occurrence, which was in accordance with a previous research (14). Possible explanations for this nding might lie in complicated diseases increasing with age and weakening the in uence of H.pylori infection on the occurrence of thyroid nodules.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…And then, the correlation between H.pylori infection and benign or suspicious TN subtypes were further analyzed in the logistic regression analysis adjusted for potential risk factors. Although the proportion of H.pylori positive population in suspicious TN group was statistically lower than that in negative population, H.pylori infection is not an independent risk factors for either benign or suspicious TN occurrence, which was in accordance with a previous research (14). Possible explanations for this nding might lie in complicated diseases increasing with age and weakening the in uence of H.pylori infection on the occurrence of thyroid nodules.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Shen et al found that H. pylori infection was positively correlated with the risk of TN (8). However, a multicenter case-control study showed that H. pylori infection was not signi cantly associated with both the risk of TN and severity of its malignant differentiation (14). In the present study, the correlation between H.pylori infection and TN subtypes prevalence was investigated in a health examination population.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, a casecontrol study including 370 cases indicated that H. pylori infection was significantly higher in patients with benign TNs than in the control group (Bakhshipour et al, 2022). However, there was also an opposite view that the association between H. pylori infection and TNs risk was a lack of sufficient evidence (Wang et al, 2021). The reasons for this discrepancy among different cohorts remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular mimicry is the mainstream hypothesis, it cannot fully explain the mechanism of TNs development. The scholars (Zhang et al, 2019;Wang et al, 2021) have proposed a complementary mechanism for dysbiosis, pointing out the induction of thyroid cancer and TNs are both associated with imbalanced composition of gut microbiome, such as an increasing proportion of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation